Government Tips In Severe Human Rights Conflicts In Political Legal: Case Study Of Papua - Wafa, Zaein (Indonesian Journal of Criminal Law, 2024)
Indonesian government has taken various measures to strengthen the status and identity of Papua, which continues to evolve with each change in administration. After the status of Papua as a Military Operations Area was revoked in 1998, a significant number of troops continue to be deployed to Papua. Numerous human rights violations persist in Papua to this day. Over the years, the government has sought to enhance security in Papua by deploying military personnel, such as the TNI and Polri. However, instead of ensuring safety in Papua, the number of casualties, both among civilians and military personnel, continues to rise. This study aims to examine the human rights conflicts experienced by the Papuan community. The research gathers descriptive data through a qualitative case study of literature. The findings indicate that human rights violations are likely to persist in Papua in the coming years. The central government of Indonesia has been criticized for its failure to establish peace and prosperity in Papua. This has led many Papuans to express a desire to leave the NKRI. Another contributing factor is the slow and often delayed judicial process, which is attributed to poorly designed components of the legal system.